Comparative analysis of wild-type and chloroplast MCU-deficient plants reveals multiple consequences of chloroplast calcium handling under drought stress - Corti, Francesca; Festa, Margherita; Stein, Frank; Stevanato, Piergiorgio; Siroka, Jitka; Navazio, Lorella; Vothknecht, Ute C.; Alboresi, Alessandro; Novák, Ondřej; Formentin, Elide; Szabò, Ildikò (Frontiers in Plant Science, 2023)
Chloroplast calcium homeostasis plays an important role in modulating the response of plants to abiotic and biotic stresses. One of the greatest challenges is to understand how chloroplast calcium-permeable pathways and sensors are regulated in a concerted manner to translate specific information into a calcium signature and to elucidate the downstream effects of specific chloroplast calcium dynamics. One of the six homologs of the mitochondrial calcium uniporter (MCU) was found to be located in chloroplasts in the leaves and to crucially contribute to drought-and oxidative stress-triggered uptake of calcium into this organelle. In the present study we integrated comparative proteomic analysis with biochemical, genetic, cellular, ionomic and hormone analysis in order to gain an insight into how chloroplast calcium channels are integrated into signaling circuits under watered condition and under drought stress. Altogether, our results indicate for the first time a link between chloroplast calcium channels and hormone levels, showing an enhanced ABA level in the cmcu mutant already in well-watered condition. Furthermore, we show that the lack of cMCU results in an upregulation of the calcium sensor CAS and of enzymes of chlorophyll synthesis, which are also involved in retrograde signaling upon drought stress, in two independent KO lines generated in Col-0 and Col-4 ecotypes. These observations point to chloroplasts as important signaling hubs linked to their calcium dynamics. Our results obtained in the model plant Arabidopsis are discussed also in light of our limited knowledge regarding organellar calcium signaling in crops and raise the possibility of an involvement of such signaling in response to drought stress also in crops.